1986
DOI: 10.1016/s0022-5347(17)45332-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Partial Ureteric Obstruction in Newborn Rats. VII. Are the Long Term Effects on Renal Morphology Avoided by Release of the Obstruction?

Abstract: Partial obstruction of the left ureter was created in newborn rats. The obstruction was either permanent or was released after two or seven days. The effects were studied at the age of six weeks. The permanently obstructed kidneys characteristically exhibited considerable enlargement (X 18) of pelvic volume and prominent deformation of the papilla, frequently associated with moderate widening of collecting ducts and convoluted tubuli, and focal inflammatory and degenerative lesions. The weight difference betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…Persistent microstructure lesions have been thought to be a source of stimulation [21], In the present series, we found mild, possibly nonspecific changes, simi lar to those previously reported as early as 1-6 weeks after release [12,13]; however, these seem too discreet to induce stimulation. Persistent /imc7/o« reduction is anoth er explanation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Persistent microstructure lesions have been thought to be a source of stimulation [21], In the present series, we found mild, possibly nonspecific changes, simi lar to those previously reported as early as 1-6 weeks after release [12,13]; however, these seem too discreet to induce stimulation. Persistent /imc7/o« reduction is anoth er explanation.…”
Section: Discussionsupporting
confidence: 88%
“…In short, the contralateral kidney increased as regards kidney weight, renal blood flow and glomerular filtration, thereby fully compensating for the moderate reductions on the ipsilateral side. In parallel studies [12,13], the obstruction was released -after 2 or 7 days. 6 weeks later, hydronephrosis was never present.…”
mentioning
confidence: 99%
“…In our studies concerning morphology, rats were obstructed at 1-2 days of age and unobstructed after 2 or 7 days [5,6,8]. When studied 6 weeks later, no signs of hydronephrosis remained.…”
Section: Introductionmentioning
confidence: 72%
“…It is unclear if these changes are avoidable or reversible by unobstruction, as this has only rarely been studied, and even more seldomly in immature animals with partial obstruction [5][6][7][8]. In our studies concerning morphology, rats were obstructed at 1-2 days of age and unobstructed after 2 or 7 days [5,6,8].…”
Section: Introductionmentioning
confidence: 97%
“…During the first 4-5 days, the glomeruli in the subcapsular layer are in the S stage [1], resembling the human fetal kidney in the last trimester [2], On the basis of autopsy studies in human fetuses, Osathanondh and Potter [3] postulated that immature nephrons are particulary susceptible to obstructive nephropathy. These authors found that par tial obstruction of the urethra caused dysplastic renal changes, whereas partial obstruction of the ureter was associated with but little renal change, possibly reflecting that, in the latter case, the obstruction is usually less severe and occurs at a later stage of fetal develop ment [4], Our own previous studies indicate that the influence of partial ureteric obstruction on the neonatal rat kidney is particularly evident during the first few days after birth [5,6], i.e. at a stage when the subcapsular nephrons are still immature [1].…”
Section: Introductionmentioning
confidence: 99%